The Analgesic Activity Study of Ethanol Extract of Plantago Major L. in Mice (Mus Musculus L.) using Writhing Test Method - Puteri, Cut Intan Annisa; Simahate, Sadjnah; Ningtias, Anggitha; Fauzi, Ziza Putri Aisyia; Karo-Karo, Sry Ulina; Andry, Muhammad (Jurnal Biologi Tropis, 2024)
Plantago major L. are known as weeds on plantations. Plantago major L. is effective to overcome pain because they contain secondary flavonoid metabolites that have the potential as pain relievers. The purpose of the experiment was to determine the analgesic effect of ethanol extract on Plantago major L. plant on male white mice. The experiment, phytochemical screening of ethanol and powder extracts from Plantago major L. plant, powder of simplicia characterization examination and analgesic effect using writhing test were carried out. As a pain inducer, 0.5% acetic acid is used intraperitoneally injected the lower abdomen of the mice and the amount of stretching is calculated with an interval of 5 minutes for 1 hour. The suspension of ethanol extract of Plantago major L. was given at a dose of 500, 1000 and 2000 mg / kg BW, 2% methampyron suspension as a positive control and 0.5% CMC suspension as a negative control. Pharmacological test results based on ANOVA test found that the amount of stretching between treatment groups was significantly different (p <0.05). The results of the analgesic effectiveness percentage obtained that the EEPM (Ethanol Extract of Plantago Major L.) suspension dose 500, 1000 and 2000 mg / kg BW had the highest analgesic power at a dose of 2000 mg / kg BW of 85.84%, EEPM suspension group 1000 mg / kg BW of 74.96 % and in the EETDS suspension group 500 mg / kg BW 62.37%.